Economic growth and suicide rates: Differential accumulated effects. - Dong-Wook Lee; Yun-Chul Hong; Je-Yeon Yun; Soo-Hyun Nam; Nami Lee (PLoS ONE, 2025)
Economic growth has a protective effect against suicide, but the nature of this association remains unclear. This ecological study explored the relationship between economic growth and suicide rates across countries within a specific timeframe. Data on age-standardized suicide rates and gross domestic product per capita (GDPpc) from 198 countries between 1991 and 2021 were obtained from the Global Burden of Disease Study and the World Bank. Using a two-way fixed-effects model and the compound annual growth rate, the association between age- and sex-adjusted suicide rates and GDPpc changes in preceding years was analyzed. GDPpc growth and lower suicide rates were significantly correlated, with a stronger correlation over longer periods, and similar associations were observed in upper-middle, lower-middle, and low-income countries. The opposite correlation was found between increased suicide rates and short-term average GDPpc growth in high-income countries, with economic growth being associated with increased suicide rates in these countries. In low- and lower-middle-income countries, increased suicide rates were associated with long-term economic stagnation. Socioenvironmental stress related to economic changes should be considered when implementing suicide prevention policies.